Heart transplantation: approaching a new century. - Radovancević, B (1999)
Although cardiac surgeons have gained considerable experience with heart transplantation during the past 30 years, this operation still presents many challenges. The number of transplant candidates continues to exceed the number of available donor hearts, and the shortage is not expected to improve. For patients fortunate enough to receive a donor heart, perioperative mortality is a serious concern. After the 1st postoperative year, the most frequent cause of death is transplant vasculopathy. Other potential complications include renal dysfunction, bleeding, infection, and allograft rejection. Despite these problems, heart transplantation remains the best hope for patients with end-stage heart failure that is unresponsive to conventional therapy. In the future, mechanical cardiac assistance and new medical treatments for end-stage heart disease may offer alternatives to heart transplantation, reducing the competition for scarce donor hearts.